Using Model‐Based "Learn and Confirm" to Reveal the Pharmacokinetics‐Pharmacodynamics Relationship of Pembrolizumab in the KEYNOTE‐001 Trial. (8th November 2016) - Elassaiss‐Schaap, J; Rossenu, S; Lindauer, A; Kang, SP; de Greef, R; Sachs, JR; de Alwis, DP
Abstract : Evaluation of pharmacokinetic/pharmacodynamic (PK/PD) properties played an important role in the early clinical development of pembrolizumab. Because analysis of data from a traditional 3 + 3 dose‐escalation design revealed several critical uncertainties, a model‐based approach was implemented to better understand these properties. Based on anticipated scenarios for potency and PK nonlinearity, a follow‐up study was designed and thoroughly evaluated. Execution of 14, 000 virtual trials led to the selection and implementation of a robust design that extended the low‐dose range by 200‐fold. Modeling of the resulting data demonstrated that pembrolizumab PKs are nonlinear at <0.3 mg/kg every 3 weeks, but linear in the clinical dose range. Saturation of ex vivo target engagement in blood began at ≥1 mg/kg every 3 weeks, and a steady‐state dose of 2 mg/kg every 3 weeks was needed to reach 95% target engagement, supporting examination of 2 mg/kg every 3 weeks in ongoing trials in melanoma and other advanced cancers.